Alveolar Differentiation Potency of Human Distal Airway Stem Cells Is Associated with Pulmonary Pathological Conditions - Yujia Wang; Yi Lu; Yingchuan Wu; Yufen Sun; Yueqing Zhou; Qiwang Ma; Yawen Zheng; Qianwen Yu; Yujie Cao; Guangdong Chen; Ting Zhang; Xiaotian Dai; et al. (Stem Cells International)
Background. This study is aimed at characterizing the human distal airway stem cells (DASCs) and assessing their therapeutic potential in patients with chronic, degenerative lung diseases. These findings will provide a comprehensive understanding for further clinical applications utilizing autologous airway stem cells as therapeutic intervention in respiratory diseases. Methods. DASCs were isolated from healthy subjects or patients diagnosed with bronchiectasis, chronic obstructive pulmonary diseases (COPD), or interstitial lung disease (ILD). Differentiation capacity, a key property of the stem cells, was studied using a novel monolayer differentiation system. The differentiated cells were evaluated for alveolar and bronchial cell marker expression, and the quantified expression level of differentiated cells was further examined for their relationship with age and pulmonary function of the subjects. Results and Conclusions. Differentiation of DASCs and tracheal stem cells (TSCs) yielded an alveolus-like structure and a tube-shaped structure, respectively, with distinct marker gene expression. Additionally, single-cell-derived clones showed diverse differentiation fates, even if the clones arise from identical or different individuals. More importantly, the alveolar differentiation potency was higher in DASCs derived from patients than from healthy people. The differentiation efficiency of DASCs also correlates with age in patients with bronchiectasis and ILD.